First spectral reflectance dataset of a highly invasive and aggressive alien plant species, Equisetum hyemale (snakegrass), in South Africa: Towards early detection and effective eradicationZenodo - Lesibana Sedibana; Mahlatse Kganyago; Thulisile Jaca; Kowiyou Yessoufou (Data in Brief)
This paper presents the first spectral reflectance dataset of snakegrass (Equisetum hyemale L.) invasive alien species recorded in South Africa. A total of 338 plant specimens were collected in Howick, KwaZulu-Natal province, and carefully stored in a cooler box for less than 24 hours of collection to retain the structural and biochemical state of the specimens and their overall characteristics. Then, spectral reflectance measurements were collected under laboratory conditions using the PSR-300 Spectral Evolution full-range spectrometer, equipped with a bifurbucated cable, a leaf clip and an artificial lighting system. Next, spectral preprocessing was performed in R statistical software to remove noisy spectra and regions and perform averaging per sample. The dataset is critical for early detection of the species and spatial distribution mapping using remotely piloted systems and earth observation satellites, providing essential information for aiding containment and eradication efforts.